Structuring privacy policy: an AI approach - Alkoby, Shani; Hirschprung, Ron S. (Frontiers in Artificial Intelligence, 2026)
IntroductionPrivacy has become a significant concern in the digital world, especially concerning the personal data collected by websites and other service providers on the World Wide Web network. One of the significant approaches to enable the individual to control privacy is the privacy policy document, which contains vital information on this matter. Publishing a privacy policy is required by regulation in most Western countries. However, the privacy policy document is a natural free text-based object, usually phrased in a legal language, and rapidly changes, making it consequently relatively hard to understand and almost always neglected by humans.MethodsThis research proposes a novel methodology to receive an unstructured privacy policy text and automatically structure it into predefined parameters. The methodology is based on a two-layer artificial intelligence (AI) process.ResultsIn an empirical study that included 49 actual privacy policies from different websites, we demonstrated an average F1-score > 0.8 where five of six parameters achieved a very high classification accuracy.DiscussionThis methodology can serve both humans and AI agents by addressing issues such as cognitive burden, non-standard formalizations, cognitive laziness, and the dynamics of the document across a timeline, which deters the use of the privacy policy as a resource. The study addresses a critical gap between the present regulations, aiming at enhancing privacy, and the abilities of humans to benefit from the mandatory published privacy policy.